Hox-Positive Adult Mesenchymal Stromal Cells: Beyond Positional Identity - Kulebyakina, Maria; Makarevich, Pavel (Frontiers in Cell and Developmental Biology, 2020)
Homeotic genes (Hox) are universal regulators of the body patterning process in embryogenesis of metazoans. The Hox gene expression pattern (Hox code) retains in adult tissues and serves as a cellular positional identity marker. Despite previously existing notions that the Hox code is inherent in all stroma mesenchymal cells as a whole, recent studies have shown that the Hox code may be an attribute of a distinct subpopulation of adult resident mesenchymal stromal cells (MSC). Recent evidence allows suggesting a “non-canonical” role for Hox gene expression which is associated with renewal and regeneration in postnatal organs after damage. In tissues with high regenerative capacity, it has been shown that a special cell population is critical for these processes, a distinctive feature of which is the persistent expression of tissue-specific Hox genes. We believe that in the postnatal period Hox-positive subpopulation of resident MSC may serve as a unique regenerative reserve. These cells coordinate creation and maintenance of the correct structure of the stroma through a tissue-specific combination of mechanisms. In this article, we summarize data on the role of resident MSC with a tissue-specific pattern of Hox gene expression as regulators of correct tissue reconstruction after injury.